[Students Sierra Madre dorm room, 1987] - Information Technology Services::::::photographer::: (1987)
The dorm room is decorated with a Top Gun poster, an Alvin and Chipmunks bed spread, a photo of the San Diego Padres' mascot 'The Chicken', and 'Go Navy' and 'I Love San Diego' stickers. Based on these decorations, the resident is presumed to be from San Diego.